2018
DOI: 10.1111/sum.12440
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation in no‐till soils modifies the soil fatty acids signature

Abstract: Analysis of whole‐soil fatty acids (WSFA) was used to characterize no‐till productive agricultural soils associated with different crop rotation managements on the Argentinean pampas, over two sampling seasons. Crop rotation (CR) treatment was compared with soybean monocropping (MC). Soils from nearby natural environments (NE) were used as reference treatments. The objective of this study was to characterize the soil lipid signature and seek putative markers of agricultural management. NE sites had greater con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…It has been previously shown for the same soils of the present study that the differences in agricultural practices modify the bacterial diversity at the regional level (Rosa et al., ); it was also possible to detect taxonomic groups of bacteria that are responders to the different agricultural practices despite the type of soil (Figuerola et al., ), and in these soils to detect differences in the fatty acid profiles of phospholipids, neutral lipids and whole soil fatty acids that discriminate between treatments (Ferrari et al., , ). Other quantitative arguments regarding levels of organic matter have shown that crop rotation compared with monocropping enhances the concentration of soil organic carbon (SOC) and carbohydrates in the soil (Duval et al., ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It has been previously shown for the same soils of the present study that the differences in agricultural practices modify the bacterial diversity at the regional level (Rosa et al., ); it was also possible to detect taxonomic groups of bacteria that are responders to the different agricultural practices despite the type of soil (Figuerola et al., ), and in these soils to detect differences in the fatty acid profiles of phospholipids, neutral lipids and whole soil fatty acids that discriminate between treatments (Ferrari et al., , ). Other quantitative arguments regarding levels of organic matter have shown that crop rotation compared with monocropping enhances the concentration of soil organic carbon (SOC) and carbohydrates in the soil (Duval et al., ).…”
Section: Discussionsupporting
confidence: 61%
“…Another influence would probably be the weather, which plays a major role in seasonal effect, as soil temperature partly influences soil activity (Davidson & Janssens, 2006). The fatty acid profiles obtained from the same soil samples as the ones used in the present work showed that both bacteria and fungi are reduced from summer to winter and that the differences between agricultural practices also become clearer in winter than in summer samples (Ferrari et al, 2015(Ferrari et al, , 2018.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Whole soil fatty acids analysis (WSFA) was run according to Ferrari et al (22). In brief, 1 g of freeze-dried and liquid N 2 milled soil sample was saponified with a NaOH-methanol mixture and methylated with HCl-methanol.…”
Section: Soil Whole Fatty Acids Lipidic Profile and Estimation Of Mic...mentioning
confidence: 99%
“…Fatty acids were analyzed through the MIDI microbial identification protocol (Sherlock R Microbial Identification System, version 6.2 and the RTSBA6 aerobe library). Nomenclature of fatty acids and grouping by chemical functions were done according to Ferrari et al (22). The concentration of each fatty acid identified by the MIDI software was assessed concerning the 19:0 standard and expressed as nmol g −1 .…”
Section: Soil Whole Fatty Acids Lipidic Profile and Estimation Of Mic...mentioning
confidence: 99%